The Variability of Proximate Composition, Sugars, and Vitamin C in Natural, Organic, and Biodynamic, and Fermented Leaves of Fireweed (Chamerion angustifolium (L.) Holub (Onagraceae)) - Marius Lasinskas; Elvyra Jariene; Nijole Vaitkeviciene; Jurgita Kulaitiene; Sonata Trumbeckaite; Aloyzas Velicka; Ewelina Hallmann (Horticulturae, 2023)
Functional foods and herbs are becoming more and more popular as a way to improve health and at the same time improve diet. One of these plants is fireweed, which is abundant in fibers, proteins, and vitamin C in addition to polyphenols and carotenoids. Limited study is being carried out and there is limited information available about how the solid-phase fermentation and different growth systems change the proximate composition, as well as quantities of vitamin C, and sugars in the fireweeds leaves. The experiment was conducted in 2022 on an organic farm (Jonava district, Lithuania). The objective of this research was to determinate the impact of various growing systems (naturally, organically, and biodynamically) and duration (24, 48, and 72 h) effect of solid-phase aerobic fermentation on the changes of fibers, ash, proteins, vitamin C, and sugars. The fibers were established using the Kjeldahl method. High-performance liquid chromatography was used for sugars and vitamin C identification. The study found significant differences in the effects of various growing systems and solid-phase fermentation on the quantitative composition of substances in the fireweed leaves. Based on the data available, it is recommended to consume fermented fireweed leaves that are organically grown and fermented for a period of 48 h as they are a good source of vitamin C and fibers. Biodynamically grown fireweed leaves are a good source of ash and proteins. Naturally grown fireweed leaves, which are not fermented, are a good source of sugars.